2017
DOI: 10.1002/adom.201700647
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐Induced Wide‐Range Reversible Emission Shift of Triphenylamine‐Substituted Anthracene via Hybridized Local and Charge Transfer (HLCT) Excited State

Abstract: 4‐(Anthracen‐9‐yl)‐N,N‐diphenylaniline (TPA‐AN) is a typical molecule belonging to a donor–acceptor system. Here, the ordered crystal and the powder of TPA‐AN are used for high‐pressure Raman and fluorescence experiments, and their spectroscopic features under the shearing force of grinding and the hydrostatic pressure applied by a diamond anvil cell (DAC) are compared. The mechanochromism of TPA‐AN is discussed in detail based on the analysis of its single‐crystal structure and pressure‐driven spectral change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…This blueshift behavior indicated that the length of aromatic C−H bonds was shortened, owing to closer molecular packing, which resulted in a loss of Raman vibration activity and intensity under high pressure . Additionally, the bands at trueν˜ ≈1608 and 2219 cm −1 could be attributed to the stretching vibrations of C=C and cyano groups, respectively, observed in both IR and Raman spectroscopy (Figure a,b) . As depicted in Figure c and d, these vibration bands shifted gradually toward high frequencies, which further implied closer packing and shortening of the distance between adjacent molecules under increasing pressure.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…This blueshift behavior indicated that the length of aromatic C−H bonds was shortened, owing to closer molecular packing, which resulted in a loss of Raman vibration activity and intensity under high pressure . Additionally, the bands at trueν˜ ≈1608 and 2219 cm −1 could be attributed to the stretching vibrations of C=C and cyano groups, respectively, observed in both IR and Raman spectroscopy (Figure a,b) . As depicted in Figure c and d, these vibration bands shifted gradually toward high frequencies, which further implied closer packing and shortening of the distance between adjacent molecules under increasing pressure.…”
Section: Resultsmentioning
confidence: 88%
“…As depicted in Figure c and d, these vibration bands shifted gradually toward high frequencies, which further implied closer packing and shortening of the distance between adjacent molecules under increasing pressure. Figure S16 in the Supporting Information indicated that the splitting and degeneration of the vibration band did not appear in the Raman and IR spectra, which suggested that no phase transition occurred during the compression process . Upon fully releasing the pressure, all bands returned to the original state, showing excellent stability and reversibility (Figure S17 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2c exhibits a gradual solvatochromism red-shift process along with the increasing solvent polarity from n-hexane (403 nm) to acetonitrile (464 nm) (listed in Table S2, Supporting Information), indicating a typical CT character of 2TPA-PPI. [41] According to the Lippert-Mataga solvatochromic model, [42] the PL spectrum with the fine vibrational structure LE-like character of 2TPA-PPI in n-hexane indicates that the dipole moment of S 1 can be estimated by the slope of the Stokes shift (ν a −ν f ) versus the solvent polarity function (f) plot. As depicted in Figure 2d, 2TPA-PPI molecule shows two-section linear fitting in low-polarity solvents and high-polarity solvents, their corresponding to two different excited-states.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…30,31 Under such a high pressure, many types of conversions on the packing ways of molecules and the luminous states can be realized, for instance, the transformation of polymorphs, 32 the switching of the intramolecular charge transfer (ICT) process, 33 the emission enhancement from the rehybridization of the nitrogen atom, 34 and the separation of the hybridized local and charge transfer (HLCT) excited state. 35 Though their pathways are different, most of them undertake reversible colour changes during the compression-decompression process. 36 So far, to our best knowledge, there are few reports on the pressure-dependent ESIPT mechanism, and the effects of pressure and/or temperature parameters on the fluorescence properties of these ESIPT fluorophores have not been well investigated in detail.…”
Section: Introductionmentioning
confidence: 99%